Tingkat Pengetahuan dan Perilaku Pasien terhadap Obat Halal di RST Dr. Soedjono Magelang - Arfianto, Erki; Pradana, Dissa Cita Sakti; Herman, Fabianus (Sultan Agung Islamic University of Semarang, 2024)
Background: Many medicines circulating in the community have unknown halal status, so it is more difficult for the public to get medicines that have a halal logo compared to food/drinks that have a halal logo. Public knowledge of halal medicines will affect their attitude in choosing or buying medicines. The purpose of this study was to determine the level of knowledge and behavior of patients at RST dr. Soedjono Magelang towards halal medicines. Methods: The sampling technique used purposive sampling with a sample size of 100 respondents using a questionnaire instrument. Results: The level of patient knowledge of halal medicines at RST dr. Soedjono Magelang ranges from 29 - 98%, with the lowest results in knowledge of the presence or absence of a halal logo on the product and low consumer knowledge of drug composition, while the level of patient behavior towards halal medicines at RST dr. Soedjono Magelang ranges from 83 - 92%. Conclusion: The level of patient knowledge and behavior towards halal medicines at RST dr. Soedjono Magelang each had an average value of 63.2% (Fair) and 87% (Very Good).